Prenatal Diagnosis of Canine and Feline Twins Using Ultrasound: A Retrospective Study - Fabiana Pecchia; Stefania Di Giorgio; Alessandra Sfacteria; Salvatore Monti; Cecilia Vullo; Giuseppe Catone; Gabriele Marino (Animals, 2023)
Prenatal diagnosis comprises a set of investigations, both instrumental and laboratory-based, which aim to monitor the health of the foetus during pregnancy, from the early stages of embryonic development to the moments preceding delivery. A growing interest is emerging for the preterm ultrasound morphological screening of embryos and foetuses, aimed at assessing the integrity and viability of the conceptus, as well as the early diagnosis of anomalies which can cause complications. This study is a retrospective study of the ultrasonographic findings of twins in the authors’ clinical activity from 2016 to 2022. Only seven cases of monochorionic twins were recorded, out of the whole number of evaluations performed on 3120 foetuses, with a prevalence of 0.6% and 0.2% in feline and canine foetuses. All the twins had their own amniotic sac and umbilical cord but presented a single placenta and a single allantoic sac. Unfortunately, the three feline cases were not more recognizable at term. In the four canine cases, three were of opposite sex and then necessarily dizygotic. Twins may have an impact on the success of a pregnancy due to the risk of dystocia, as observed in some of the reported cases. Prenatal ultrasound allows early recognition of twins in dogs and cats.